(untitled) (American Journal of Islam and Society, 1999)
James Robertson is a seasoned policy maker. More than three decades ago, from the corridors of Whitehall, he became the architect of the "winds of change" theme for British Prime Minister Harold Macmillan’s end-of-empire tour of Africa. Robertson’s theme of change is a call for liberation, and more specifically, liberation from the control and domination of institutional power. He sees it fit to argue that in the post-imperial world, prosperity and survival of nations and peoples depends on a deep-rooted concern for humans and nature. In the postmodern world where communism has breathed its last and socialism is in disrepute, Robertson has attempted to chart a new course for the future of humanitv. lie believes that both caQ.italism and socialism have served the motives of big businesses and state. It is time for a postmodern worldview to emerge that will rectify the excesses of the two dominant systems. The author calls for a new path of progress, based on co-operative self-reliance rather than increased dependency, so that the world allows people (and nations) to take responsibility for their own development in co-operation with one another. He sees this not only as an important end in itself, but also as "the only means, barring worldwide catastrophe, of transforming today’s ecologically destructive patterns of human activity into ways of life that can be sustained into the future" (p. xi). This theme constitutes the bulk of lectures and papers that are reprinted in the book. Spanning a period of nearly two decades - from 1977 to 1996 - they complement the author’s earlier published works: The Sane Alternative ...